Mid-term study of transcatheter aortic valve implantation in an Asian population with severe aortic stenosis: two-year Valve Academic Research Consortium-2 outcomes - Chew, Nicholas (Singapore Med J, 2017)
INTRODUCTION: Transcatheter aortic valve implantation (TAVI) is an effective treatment for high-risk or inoperative patients with severe aortic stenosis. Given the unique characteristics of Asian populations, questions regarding mid-term outcomes in Asians undergoing TAVI have yet to be addressed. We evaluated the two-year clinical outcomes of TAVI in an Asian population using Valve Academic Research Consortium-2 definitions. METHODS: This prospective study recruited 59 patients from a major academic medical centre in Singapore. The main outcomes were two-year survival rates, peri-procedural complications, symptom improvement, valvular function and assessment of learning curve. RESULTS: Mean age was 76.8 years (61.0% male), mean body surface area 1.6 m(2) and mean logistic EuroSCORE 18.7%. Survival was 93.2%, 86.0% and 79.1% at 30 days, one year and two years, respectively. At 30 days post TAVI, the rate of stroke was 1.7%, life-threatening bleeding 5.1%, acute kidney injury 25.0%, major vascular complication 5.1%, and new permanent pacemaker implantation 6.8%. 29.3% of TAVI patients were rehospitalised (47.1% cardiovascular-related) within one year. These composite outcomes were measured: device success (93.2%); early safety (79.7%); clinical efficacy (66.1%); and time-related valve safety (84.7%). Univariate analysis found these predictors of two-year all-cause mortality: logistic EuroSCORE (hazard ratio [HR] 1.07; p < 0.001); baseline estimated glomerular filtration rate (HR 0.97; p = 0.048); and acute kidney injury (HR 5.33; p = 0.022). Multivariate analysis identified non-transfemoral TAVI as a predictor of cardiovascular-related two-year mortality (HR 14.64; p = 0.008). CONCLUSION: Despite the unique clinical differences in Asian populations, this registry demonstrated favourable mid-term clinical and safety outcomes in Asians undergoing TAVI.